The professionals : strategy, money & the rise of the political campaigner in Australia - Mills, Stephen (Black Incorporated, 2014)
Stephen Mills has conducted on-the-record interviews with every living national campaign director of the two major political parties. Their experience covers the 15 federal election campaigns from 1974 to the present day. Built around twelve critical moments in Australian electoral history, The Professionals traces the transformation of the party official from administrative servant to highly influential, professional campaign manager, and the election campaign from the pre-television days to the contemporary world of social media, focus groups and million-dollar budgets. He shows how Australia.